Asymptotic expansions for the number of realizations of recurrent event - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкявичене. Асимптотическое разложение для распределения числа появлений рекуррентного события A. Aleškevičienė. Rekurentinių įvykių pasirodymo skaičiaus pasiskirstymų asimptotiniai išdėstymai